Accidental and Intentional Exporters : Comparing Indonesian and Malaysian MSMEs. - Yean, Tham Siew (ISEAS - Yusof Ishak Institute, 2018)
Regardless of the size of the domestic economy, there are ample reasons for firms to extend their markets beyond home shores. These include increasing sales, improving profits, diversifying risks, reaping economies of scale, matching the moves of competitors, enhancing competitiveness or accessing government incentives. Both Indonesia and Malaysia seek to enhance the competitiveness of their micro, small and medium enterprises (MSMEs) by including internationalization goals in their respective national development plans for these enterprises. Findings from fourteen case studies in the two countr.